Spiritual Distress in Patients With Cancer Initiating Chemotherapy: A Cross‐Sectional Study. Issue 5 (26th July 2021) - Martins, Helga; Caldeira, Sílvia; Vieira, Margarida; Campos de Carvalho, Emília; Flanagan, Jane
Abstract: Purpose: To assess spiritual distress in patients with cancer who were initiating chemotherapy. Methods: This was a quantitative, observational, cross‐sectional study. Data collection was conducted between February and June of 2019. The Spiritual Distress Scale (SDS) was administered to 332 patients with cancer. Findings: Most participants (56.6%) were female, with the mean age at 60.3 years ( SD = ±11.73). The mean SDS score was 56.6 ( SD = ±13.39), with 30% of the participants reporting moderate and 9.6% reporting high levels of spiritual distress. Younger age (β = ‐0.687, p = .008) and participants having no religious affiliation were predictors of SDS (β = ‐8.322, p = .035) in patients with cancer initiating chemotherapy. Conclusions: Given the degree of spiritual distress reported, this study provides further evidence to support the need for nurses to assess spirituality in order to provide holistic care inclusive of spiritual domain. Clinical Relevance: These results are relevant to clinical practice and indicate a need for nurses to use the clinical reasoning process to assess spiritual distress and to plan nursing interventions aimed at meeting the spiritual needs of patients with cancer who are initiating chemotherapy.